2016
DOI: 10.1051/matecconf/20168201019
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Prediction in Grinding: a Probabilistic Approach

Abstract: Abstract. Surface quality of machined components is one of the most important criteria for the assessment of grinding processes. The importance of surface finish of a product depends upon its functional requirements. Since surface finish is governed by many factors, its experimental determination is laborious and time consuming. So the establishment of a model for the reliable prediction of surface roughness is still a key problem for grinding. In this study, a new analytical surface roughness model is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…A number of models have been constructed by several authors with different assumptions summarized in Table 1. T he cross-section of the scratches of each abrasive brain left on the surface workpiece is semi-circular shape (4) 5 = 0.92 * ℎ Krishna Kumar Saxena et al [7] T he cross-section of the scratches of each abrasive brain left on the surface workpiece is semi-circular shape (5) In the above formulas, hm is the undeform chip thickness. The value of hm depends on many parameters s uch as cutting parameters, grinding wheel type, grain size, etc, and is defined as follows [8]:…”
Section: Some Models Predict the Surface Roughness Of Workpiece When Grindingmentioning
confidence: 99%
“…A number of models have been constructed by several authors with different assumptions summarized in Table 1. T he cross-section of the scratches of each abrasive brain left on the surface workpiece is semi-circular shape (4) 5 = 0.92 * ℎ Krishna Kumar Saxena et al [7] T he cross-section of the scratches of each abrasive brain left on the surface workpiece is semi-circular shape (5) In the above formulas, hm is the undeform chip thickness. The value of hm depends on many parameters s uch as cutting parameters, grinding wheel type, grain size, etc, and is defined as follows [8]:…”
Section: Some Models Predict the Surface Roughness Of Workpiece When Grindingmentioning
confidence: 99%
“…(10) ( ) = 0.92 (ℎ), [15] Hypothesis was that shapes of scratches of the grinding particles leaving on the workpiece surface was the curved arc of a quarter circle. (11) The above cited surface roughness models showed that depending on the different hypotheses about the shapes of the scratches of the grinding grains left on the workpiece surface.…”
Section: Modelsmentioning
confidence: 99%
“…The studies in this field have been carried out by many researchers, such as building models to predict surface roughness when grinding based on the analysis models of cutting thickness [2]; prediction the surface roughness when grinding with the assumption that the grits are uniformly distributed on the grinding wheel surface [3][4][5]; prediction the surface roughness when grinding through determining the average value of the depth of the cut into the machining surface of the abrasive grains [6]; applying probability theory when analyzing the cutting process of abrasive Engineering grains to predict surface roughness [7]; prediction surface roughness with the assumption that the grinding process is a mechanical -thermal equilibrium process [8]; build the relationship between surface roughness and unformed chip thickness when it was assumed that the cross section of each cut is made by an abrasive left on the surface of the workpiece with different geometric shapes (triangle, semicircular, curved, hyperbole) [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%